Berkreasi dengan Canva: Pelatihan Desain Grafis untuk Kreativitas Siswa MTs Sinoa - Askar, Muh.Askar; Suhardiman Suhardiman; Ahmad Nurul Ikhsan B (Penerbit Goodwood, 2025)
Purpose: This community service activity aims to equip students of MTs Sinoa with foundational knowledge and skills in graphic design using the Canva application. The training introduced students to the process of account creation, familiarization with Canva's features, and basic steps in producing a design. Research methodology: The training employed a knowledge transfer method using a service-learning approach. This method ensures a direct impact by enhancing students' familiarity with technological tools, particularly in the area of graphic design, fostering their readiness for digital-based educational and professional environments. Results: The training provided significant benefits to students, preparing them to navigate future technological advancements, especially in creative fields. Students demonstrated improved competence in operating Canva and were able to implement the learned skills during practical sessions, showing progress in both understanding and creativity. Conclusions: This activity successfully achieved its objectives. Students showed mastery in operating Canva and effectively applied the material during the hands-on sessions. The training met its educational goals, as evidenced by the students’ ability to navigate and use Canva features with confidence, indicating a strong grasp of the material. Limitations: Despite its success, this activity faced challenges, particularly in terms of student engagement. Many students showed limited interest in graphic design because of their preference for using gadgets primarily for gaming, which affected their motivation to develop both hard and soft skills. Contribution: This training supports the development of digital literacy and creativity among students, provides essential skills for future education, and contributes to the advancement of technology-based learning in schools.